2014
DOI: 10.1007/s11033-014-3334-z
|View full text |Cite
|
Sign up to set email alerts
|

No impact of SLCO1B1 521T>C, 388A>G and 411G>A polymorphisms on response to statin therapy in the Greek population

Abstract: Interindividual variability exists in statin lipid-lowering response, partially attributed to genetic factors. Organic anion-transporting polypeptide 1B1 (OATP1B1) encoded by SLCO1B1 gene (solute carrier organic anion transporter family member 1B1) facilitates hepatic uptake of simvastatin and atorvastatin. SLCO1B1 polymorphisms are strongly associated with statin-induced myopathy whereas few studies have assessed their effect on statin differential response. In the present study, we analyzed the association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…We did not find significant genetic predictors of LPV plasma concentration. Several studies among Caucasians [18,[26][27][28][29][30] have reported an association of CYP3A4*22 with increased drug plasma concentrations for drugs that are substrates of CYP3A4, however, in this cohort, the allele was absent (0%) yet LPV plasma concentration variability was still huge (>1800-fold). This shows that there could still be some variants in CYP3A4 among African populations that need to be discovered and reported.…”
Section: Correlation Between Genetic Variation and Lopinavir Dispositionmentioning
confidence: 65%
See 1 more Smart Citation
“…We did not find significant genetic predictors of LPV plasma concentration. Several studies among Caucasians [18,[26][27][28][29][30] have reported an association of CYP3A4*22 with increased drug plasma concentrations for drugs that are substrates of CYP3A4, however, in this cohort, the allele was absent (0%) yet LPV plasma concentration variability was still huge (>1800-fold). This shows that there could still be some variants in CYP3A4 among African populations that need to be discovered and reported.…”
Section: Correlation Between Genetic Variation and Lopinavir Dispositionmentioning
confidence: 65%
“…OATP1B1 (coded for by SLCO1B1 gene) is involved in the hepatic uptake of many substrates and plays an important role in transporting LPV [11][12][13], thus, genetic variation in SLCO1B1 is likely to affect LPV plasma variability. SLCO1B1 c.521T>C was monomorphic in this African cohort yet its effects on disposition of statins has been extensively reported among Caucasians, African-Americans [28][29][30][31] and Asians [32]. We cannot rule out a role for SLCO1B1 genetic variation in LPV plasma variability, but, can deduce that there could be other African-specific variants that have not yet been reported that need to be investigated.…”
Section: Correlation Between Genetic Variation and Lopinavir Dispositionmentioning
confidence: 77%
“…This pattern in descending order stands for the two polymorphisms as follows: 154 bp for 411A, 142 bp for 388A, 132 bp for 411G and 119 bp for 388G. 14 For SLCO1B1 rs4149056, the tetra primer used in ARMS-PCR with slight modifications. 15 Because the restriction endonuclease was unnecessary, the PCR products were detected by means of 2% agarose gel with electrophoresis and by ethidium bromide staining.…”
Section: Rs2306283mentioning
confidence: 99%
“…The same study cohort has also been genotyped for CYP3A4*22, CYP3A5*3 and SLCO1B1 521T>C and 388A>G by use of methods already described elsewhere [20][21][22].…”
Section: Other Gene Polymorphismsmentioning
confidence: 99%